Surface chemical and physical modification in stent technology for the treatment of coronary artery disease - Nazneen, F.; Herzog, G.; Arrigan, Damien; Caplice, N.; Benvenuto, P.; Galvin, P.; Thompson, M. (Wiley, 2012)
Coronary artery disease (CAD) kills millions of people every year. It results from a narrowing of the arteries (stenosis) supplying blood to the heart. This review discusses the merits and limitations of balloon angioplasty and stent implantation, the most common treatment options for CAD, and the pathophysiology associated with these treatments. The focus of the review is heavily placed on researchefforts geared toward the modification of stent surfaces for the improvement of stent-vascular compatibility and the reduction in the occurrence of related pathophysiologies. Such modifications may be chemical or physical, both of which are surveyed here. Chemical modifications may be passive or active, while physical modification of stent surfaces can also provide suitable substrates to manipulate the responses of vascular cells (endothelial, smooth muscle, and fibroblast). The influence of micro- and nanostructured surfaces on the in vitro cell response is discussed. Finally, future perspectives on the combination of chemical and physical modifications of stent surfaces are also presented.